Acute Cellular Rejection in Heart Transplant Patients: Insights of Global Longitudinal Strain, Myocardial Work, and an Exclusive Group of Chagas Disease - Otto, Maria Estefânia Bosco; Martins, Aline Maria Araújo; Campos Dall’Orto, Aline de Oliveira Martins; Leite, Simone Ferreira; de Queiroz Mauricio Filho, Marco Antonio Freitas; Martins, Natalia Taveira; de Araújo, Samuel Rabelo; Almeida, Soraya Vasconcelos; Paiva, Mariana Ubaldo Barbosa; Atik, Fernando Antibas (Frontiers in Cardiovascular Medicine, 2022)
Background Echocardiographic markers associated with asymptomatic acute cellular rejection (ACR) in patients with orthotopic heart transplant (HT) are still under investigation. The aim of our study was to determine clinical and myocardial strain imaging (MSI) variables evaluated by echocardiography associated with ACR in the first year of HT. A separate analysis was performed to compare variables during the first 6 months of HT, when ACR has a prevalence in 60% of patients. Another analysis evaluated an exclusive population with Chagas disease as the cause of HT. Methods We prospectively studied 67 patients with less than 1 year of HT, 36 patients without ACR (41% men, age 49 ± 12 years, 52% Chagas disease as the cause of heart failure), and 31 patients with ACR (59% men, age 55 ± 8 years, 74% Chagas disease as the cause of heart failure). Conventional echocardiographic measurements and MSI by global longitudinal strain (GLS) from the left ventricle (LV) and right ventricle free wall (RV-FWLS) and myocardial work (MW) from the left ventricle were obtained by experienced echocardiologists. Clinical variables, such as the presence of diabetes, hypertension, and immunosuppressant drugs, were compared between groups. Results HT patients with ACR were older and used more cyclosporine for immunosuppression. The positive ACR group had an increased relative wall thickness and LV mass index and similar LVGLS and RV-FWLS compared to the negative ACR group. Nevertheless, MW analysis observed increased global work efficiency (GWE) in positive ACR. Multivariate analysis identified older age, cyclosporine use, LV mass index, and GWE as independent predictors for detecting rejection. A separate analysis was performed for patients with less than 6 months of HT. Similar MSI was observed in both groups, with a trend for increased GWE in patients with ACR and significantly increased LV mass index in the ACR group. An exclusive group of Chagas patients as the primary cause of HT was analyzed, and similar MSI results for LVGLS, RV-FWLS, and MW were observed for both ACR and the no rejection groups. Additionally, the survival rates at 2 years were similar between the Chagas disease groups. Conclusion LVGLS and RV-FWLS were similar between patients with or without ACR in the first year after HT. Conversely, GWE, a derivative of LVGLS, and LV mass index were increased in positive ACR and could be markers for rejection. Increased LV mass index was also found in a subgroup analysis of patients less than 6 months after HT; however, MSI was similar regardless of ACR. For chagasic patients, rejection in the first year did not increase mortality at the 2-year follow-up, and MSI parameters were similar between patients with or without ACR. In a multivariate analysis to predict ACR, the independent parameters in this study were older age, cyclosporine use, LV mass index, and GWE.